THE CONCEPT OF POWER OVER MOVEABLE PROPERTY (BEZIT) IN CIVIL AND CRIMINAL LAW PERSPECTIVE - Isdiyana kusuma ayu; Isdian Anggraeny (Universitas Muhammadiyah Tangerang, 2021)
The issue of the position of power over movable property often raises the question of whether the party in control is the owner. This is very important in the realm of law, especially if an object that is controlled by one party will be made the object of a transaction with another person. Therefore, it is necessary to carry out further legal identification and analysis related to the concept of the position of control of the movable property, both in the perspective of civil law and criminal law so that in the end it can find differences and similarities in the concept of the position of control of the movable property so that it can create legal certainty and protection for the public. parties involved in an engagement or legal relationship. Therefore, the implementation of control of objects in civil law cannot be separated from the provisions in criminal law which ultimately require pawnshops to apply the principle of prudence in control of objects.